2011
DOI: 10.1111/j.1460-2695.2010.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack propagation behaviour of Al-Zn-Ce alloys

Abstract: A B S T R A C T This paper presents the investigation on fatigue crack growth behaviour of Al-Zn andAl-Zn-Ce alloys. Fatigue tests were carried out on as-cast and heat-treated CT specimens according to ASTM E647 testing standard. The test results showed that the addition of rare earth element (cerium) and heat treatments (T6 and T5) had very strong influence on fatigue strength. This enhancement was due to metallurgical changes in the alloy system. Cerium eliminates the porosities and refines microstructures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It has been shown that various microstructural features such as grain size, precipitates, and PFZ influence the FCGR behavior. 19,45,46 The measured grain sizes in both T6 and RRA-treated alloys were almost similar and about 10 μm. Since both heat treatments, ie, RRA and T6, were carried out following the same solution treatment temperature and low temperature aging, the presence of Al 3 Zr dispersoids (as shown in SAED in Figure 2C) acts as pinning sites on the grain boundaries.…”
Section: Effect Of the Rra On The Fatigue Crack Propagation Behaviormentioning
confidence: 75%
See 1 more Smart Citation
“…It has been shown that various microstructural features such as grain size, precipitates, and PFZ influence the FCGR behavior. 19,45,46 The measured grain sizes in both T6 and RRA-treated alloys were almost similar and about 10 μm. Since both heat treatments, ie, RRA and T6, were carried out following the same solution treatment temperature and low temperature aging, the presence of Al 3 Zr dispersoids (as shown in SAED in Figure 2C) acts as pinning sites on the grain boundaries.…”
Section: Effect Of the Rra On The Fatigue Crack Propagation Behaviormentioning
confidence: 75%
“…Hence, intrinsic mechanism of crack growth itself is expected to cause reduction in the growth rates in the RRA‐treated aluminum alloy. It has been shown that various microstructural features such as grain size, precipitates, and PFZ influence the FCGR behavior . The measured grain sizes in both T6 and RRA‐treated alloys were almost similar and about 10 μm.…”
Section: Resultsmentioning
confidence: 99%